Use of newcomb-benford law: a contribution to accounting compliance audit in the federal network of professional and technological education - Oliveira da Silva, Jailson; Rodrigues Boente, Diego (Advances in Scientific and Applied Accounting, 2023)
Objective: This study aims to analyze the accounting compliance of budgetary and property expenses of the Federal Network of Professional and Technological Education, using the methodology of the Newcomb-Benford Law. Method: A descriptive study was carried out with a quantitative approach, using the z, chi-square and Mean Absolute Deviations tests, using secondary data on budgetary and property expenditures from 42 institutions that make up the Federal Network of Professional and Technological Education. The collected data from 2017 to 2020 was extracted using the Treasury Management system. Results/Discussion: The results showed that there was a trend of growing compliance of consolidated budget data in relation to the Newcomb-Benford Law in the period from 2017 to 2019, pointing to a possible improvement in the quality of accounting information over these years. However, it is possible to observe distortions in the analyzed values, which may be associated with errors, fraud or particular characteristics of the entities’ transactions. The results point to the possibility of using the Newcomb-Benford Law as an important technique in audit work in the Federal Network of Professional and Technological Education. Contributions: Considering that the Brazilian public sector lacks data integration, the study advances in the discussion on the use of the Newcomb-Benford Law as an accounting compliance audit tool, contributing to audit planning and asset control and budget execution. In addition, the signaling of distortions in accounting data (red flags) are risk indicators and can demonstrate a situation of irregularity in real time.